2015
DOI: 10.1186/s13052-015-0171-1
|View full text |Cite
|
Sign up to set email alerts
|

Are high cumulative doses of erythropoietin neuroprotective in preterm infants? A two year follow-up report

Abstract: BackgroundPreterm infants are at risk for neurodevelopmental sequelae even in absence of major cerebral lesions. The hypothesis that Human Recombinant Erythropoietin (rEpo) could improve the neurodevelopmental outcome in risk neonates has raised the highest interest in recent years.MethodsA group of preterm neonates born at a gestational age ≤ 30 weeks and free from major cerebral lesions or major visual impairment, were included in the study if they had a complete neurologic evaluation for at least 24 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…ESAs are essential for normal brain development and augment a variety of potential neuroprotective mechanisms including promoting neurogenesis and angiogenesis ( 3 4 ) and inhibiting apoptotic, excitotoxic and oxidative injury to neurons and oligodendroglia ( 5 11 ). ESAs may improve neurologic outcome of term infants with hypoxic ischemic encephalopathy ( 12 ), and appear safe in premature infants as well ( 13 ), decreasing major morbidity ( 14 ) and possibly improving cognitive outcome at 18–22 months ( 15 ), 3.5–4 years ( 16 ) and at 10 years ( 17 ), though some trials reporting no difference have been published ( 18 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…ESAs are essential for normal brain development and augment a variety of potential neuroprotective mechanisms including promoting neurogenesis and angiogenesis ( 3 4 ) and inhibiting apoptotic, excitotoxic and oxidative injury to neurons and oligodendroglia ( 5 11 ). ESAs may improve neurologic outcome of term infants with hypoxic ischemic encephalopathy ( 12 ), and appear safe in premature infants as well ( 13 ), decreasing major morbidity ( 14 ) and possibly improving cognitive outcome at 18–22 months ( 15 ), 3.5–4 years ( 16 ) and at 10 years ( 17 ), though some trials reporting no difference have been published ( 18 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…16 Most clinical follow-up studies on preterm infants primarily treated with rhEPO (or its higherglycosylated derivate darbepoetin) for anemia of prematurity indicated improved neurodevelopmental outcomes, 17 -21 whereas only a few studies have shown no effect. 22,23 In 2005, the first phase I and II trials were initiated to establish the safety of early high-dose rhEPO for neuroprotection. 24,25 So far, only a limited number of randomized controlled trials (RCTs) have reported data on the neuroprotective effects of rhEPO in preterm infants.…”
mentioning
confidence: 99%
“…Detailed characteristics of the included studies were presented in Table 1 [13–22] . All these studies were published from 2010 to 2020.…”
Section: Resultsmentioning
confidence: 99%
“…Detailed characteristics of the included studies were presented in Table 1. [13][14][15][16][17][18][19][20][21][22] All these studies were published from 2010 to 2020. The sample size ranged from 53 to 1285.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation